2002
DOI: 10.1128/cmr.15.2.294-309.2002
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity toMycobacterium tuberculosis

Abstract: The different manifestations of infection with Mycobacterium tuberculosis reflect the balance between the bacillus and host defense mechanisms. Traditionally, protective immunity to tuberculosis has been ascribed to T-cell-mediated immunity, with CD4+ T cells playing a crucial role. Recent immunological and genetic studies support the long-standing notion that innate immunity is also relevant in tuberculosis. In this review, emphasis is on these natural, innate host defense mechanisms, referring to experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
299
1
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(319 citation statements)
references
References 254 publications
6
299
1
13
Order By: Relevance
“…It has long been recognized that lactoferrin exerts effects on a variety of leukocytes, including macrophages [55][56][57], the main host cell for both BCG and MTB [58,59]. Previous studies demonstrated that lactoferrin is capable of enhancing BCG-infected macrophage production of IL-12:IL-10 ratio [34], thus generating a cytokine environment that is favorable for promotion of T H 1 immunity [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that lactoferrin exerts effects on a variety of leukocytes, including macrophages [55][56][57], the main host cell for both BCG and MTB [58,59]. Previous studies demonstrated that lactoferrin is capable of enhancing BCG-infected macrophage production of IL-12:IL-10 ratio [34], thus generating a cytokine environment that is favorable for promotion of T H 1 immunity [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogens such as M. tuberculosis may elicit release of CXCR3-signaling chemokines from tissue macrophages and immature dendritic cells at the site of infection after recognition by TLR4 [37][38][39]. In addition, mycobacterial signaling via TLR2/TLR6 elicits chemokines that attract PMN [40][41][42][43]. PMN, in turn, guarantee both amplified attraction of T cells and focusing of the reaction to the site of infection via their secretion of CXCR3-signaling chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…The control and resolution of the infection involve the activation of macrophages, in which activated T lymphocytes play a crucial role [4]. The release of proinflammatory cytokines such as IL-1b, TNF, IL-12 or IL-18 from monocytes and monocyte-derived macrophages induces the production of T-cell-derived cytokines, most importantly IFN-g, which in turn will activate macrophages for the killing and elimination of the microorganisms [5,6].…”
Section: Introductionmentioning
confidence: 99%